The Effect of Augmented Reality on Improving Arabic Vocabulary Mastery in SMP Al-Azhar Medan Students - Nurazizah Bancin; Abdur Rahman Purba; Zulfahmi Lubis; Raihan Akbarina (Raja Zulkarnain Education Foundation, 2026)
This study aims to examine the effect of Augmented Reality (AR) on the improvement of Arabic vocabulary mastery among eighth-grade students at SMP Al-Azhar Medan. The population of this study included all eighth-grade students in the 2024/2025 academic year, with samples selected using purposive sampling to ensure comparable initial abilities. Two homogeneous classes were assigned as the experimental group, which received AR-based instruction, and the control group, which followed conventional teaching methods based on lectures and written exercises. The primary research instrument was a vocabulary test measuring recognition, comprehension, and contextual use of mufradat. Additionally, observation sheets were employed to assess student engagement during learning, and a student perception questionnaire was used as supporting data. Data were analyzed using descriptive statistics to calculate means, pretest-posttest differences, and standard deviations, as well as inferential statistics using an independent sample t-test to determine the significance of differences between the two groups. The results indicate that the experimental group achieved a significantly higher posttest mean score (84.5) compared to the control group (71.8), with a significance value of 0.001. These findings suggest that AR strengthens visual memory, enhances student motivation and engagement, and facilitates contextual internalization of vocabulary. Teachers are encouraged to integrate AR in mufradat instruction, while schools should provide technological support. Further research is recommended to evaluate the effectiveness of AR for other language skills and at different educational levels.